2009
DOI: 10.3171/2008.10.spi08495
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of decompression in functional recovery of ex vivo spinal cord white matter

Abstract: Object The correlations between functional deficits, the magnitude of compression, and the role of sustained compression during traumatic spinal cord injury remain largely unknown. Thus, the functional outcome of this type of injury with or without surgical intervention is rather unpredictable. To elucidate how severity and duration of compression affect cord function, the authors have developed a method to study electrophysiological characteristics and axonal membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…These data, when considered in the context of the above studies, are perhaps consistent with hypothermia having a small beneficial effect when applied immediately after SCI without continuing cord compression. However, we observed a significant difference of just over 2 points on the BBB scale between the normothermia and hypothermia groups decompressed at 2 h, and around a 4-point difference between the groups decompressed at 8 h. This demonstrates that hypothermia has increasing relative benefit with increasing time to decompression, and may indicate that hypothermia has the greatest influence on secondary injury processes associated with compression, such as ischemia (discussed above), and axonal membrane damage (Ouyang et al, 2009). The relatively small difference seen between groups undergoing immediate decompression may be consistent with hypothermia having less influence on secondary injury processes not directly related to compression (e.g., oxidative stress, inflammation, and apoptosis).…”
Section: Comparison With Previous Studies Of Hypothermia In Scimentioning
confidence: 55%
“…These data, when considered in the context of the above studies, are perhaps consistent with hypothermia having a small beneficial effect when applied immediately after SCI without continuing cord compression. However, we observed a significant difference of just over 2 points on the BBB scale between the normothermia and hypothermia groups decompressed at 2 h, and around a 4-point difference between the groups decompressed at 8 h. This demonstrates that hypothermia has increasing relative benefit with increasing time to decompression, and may indicate that hypothermia has the greatest influence on secondary injury processes associated with compression, such as ischemia (discussed above), and axonal membrane damage (Ouyang et al, 2009). The relatively small difference seen between groups undergoing immediate decompression may be consistent with hypothermia having less influence on secondary injury processes not directly related to compression (e.g., oxidative stress, inflammation, and apoptosis).…”
Section: Comparison With Previous Studies Of Hypothermia In Scimentioning
confidence: 55%
“…We hypothesize that a similar effect might be occurring at the compressed lesion, whereby ion channel derangement may play a factor in conduction block. Additionally, we have shown that membrane damage is only a small contributor in quasi-static compressive trauma (Ouyang et al, 2009). These clues direct us towards other mechanisms of damage, possibly related to ion channel disruptions.…”
Section: Introductionmentioning
confidence: 61%
“…Compressive deformation was performed with the multimodal soft tissue tester developed in previous studies (Ouyang et al, 2008(Ouyang et al, , 2009. A standard double sucrose gap chamber was implemented in the testing system to record the electrophysiological response of ventral white matter during mechanical loading (Shi and Borgens, 1999;Shi and Whitebone, 2006;Fig.…”
Section: Sustained Compression and Decompression Of Ventral White Matmentioning
confidence: 99%
“…For instance, studies conducted on ex vivo spinal cord samples demonstrated that 60% compression at a measured rate of 0.05 mm/sec yields only a 2% reduction in CAP amplitude (Ouyang et al, 2009). In the present study, severe blast loading produced a 60% compression at a rate of 60 m/sec with a resulting 60% reduction in conduction.…”
Section: Discussionmentioning
confidence: 97%